Proceedings of the ACM/IEEE 19th International Conference on Model Driven Engineering Languages and Systems 2016
DOI: 10.1145/2976767.2976787
|View full text |Cite
|
Sign up to set email alerts
|

Partial loading of XMI models

Abstract: XML Metadata Interchange (XMI) is an OMG-standardised model exchange format, which is natively supported by the Eclipse Modeling Framework (EMF) and the majority of the modelling and model management languages and tools. Whilst XMI is widely supported, the XMI parser provided by EMF is inefficient in some cases where models are readonly (such as input models for model query, model-to-model transformation, etc) as it always requires loading the entire model into memory. In this paper we present a novel algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…It would be interesting to find out ways to reduce its impact. At the pre-processing level, it would be possible to filter the input model at loading time using approaches like partial model loading [27]. This would enable the engine to start the transformation without waiting for the model to be fully loaded.…”
Section: Additional Optimizationsmentioning
confidence: 99%
“…It would be interesting to find out ways to reduce its impact. At the pre-processing level, it would be possible to filter the input model at loading time using approaches like partial model loading [27]. This would enable the engine to start the transformation without waiting for the model to be fully loaded.…”
Section: Additional Optimizationsmentioning
confidence: 99%
“…(2) Effective Metamodel The output of static analyser is in the form of an effective metamodel for each model involved in the program. The concept of effective metamodel was introduced in [17] in order to support partial loading of XMI files. As for partial loading, we need only the parts of the model which are accessed by the program.…”
Section: Approachmentioning
confidence: 99%
“…SmartSAX is another prototype which was introduced in [17]. It supports partial loading of XMI model files.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, even a simple query or a small change requires loading the entire model in memory at once: this is impractical for large models. Recent work by Wei et al [33] demonstrated a specialization of the EMF XMI parser which can load only the subset required by the query to be run: while this reduced loading times and memory usage, changes in the partially loaded models cannot be saved back without losing information.…”
Section: File-based Model Persistencementioning
confidence: 99%